Review: The Gospel of Mark. A Socio‐Rhetorical Commentary - Telford, William R. 1946- (2002)
The Gospel of Mark. A Socio‐Rhetorical Commentary Ben Witherington III xxi + 463 Grand Rapids, MI and Cambridge, UK Eerdmans 2001 Paperback$35/£23.99 0 8028 4503 7
Keywords: Rezension